Atrial Flutter—Unique Arrhythmia in Neonatal Population, Presentation of 3 Cases. (December 2020) - Kędziora, Piotr; Stasiak, Aleksandra
Abstract : Background: Atrial flutter (AFL) is an uncommon arrhythmia in the pediatric population. It is defined as fast ordered atrial depolarization (about 250-500 beats/min). It occurs mainly in children with congenital heart defects; however, it may also manifest in fetuses and infants with an anatomically healthy heart. In neonates, AFL is most often revealed within the first 2 days after birth. Clinical Findings: In this case report, we present 3 neonates without complex congenital heart defects with AFL, along with the description of the course, diagnostic and therapeutic processes depending on the clinical condition of a child, and response to treatment. Primary Diagnosis: Symptoms in this group of patients are nonspecific, that is, tachypnea, unwillingness to eat, and fatigue while feeding. The diagnostic process included thorough electro- and echocardiographic assessments. Each child was treated individually due to a different cause of arrhythmia and comorbidities. Interventions: Invasive (electrical cardioversion) and pharmacological methods were used in treatment to achieve conversion to sinus rhythm. Outcomes: One patient required electrical cardioversion, one was treated with amiodarone and digoxin, and one infant received amiodarone. All children achieved conversion to sinus rhythm. Practice Recommendations: During the follow-up, each child maintained sinus rhythm, which shows that in the neonatal group, it is a unique, but well-controlled, arrhythmia once conversion to sinus rhythm is achieved.